2016
DOI: 10.1176/appi.neuropsych.15090237
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structural Relationship Between Interviewer and Self-Rated Affective Symptoms in Huntington’s Disease

Abstract: This study explores the structural relationship between self-report and interview measures of affect in Huntington's disease. The findings suggest continued use of both to recognize the multidimensionality within a single common consideration of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, even though some studies have reported reasonable agreement between self-reports of HD patients and reports of their informants regarding apathy (5,22,23) and irritability (22), other studies have demonstrated that discrepancies between patient and informant ratings typically increase over time (15)(16)(17)(24)(25)(26). Such discrepancies may be caused by deteriorating insight into symptoms (27); loss of motor skills required to complete paper-based assessments; and worsening memory, which hinders the retention and retrieval of relevant information (21,28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though some studies have reported reasonable agreement between self-reports of HD patients and reports of their informants regarding apathy (5,22,23) and irritability (22), other studies have demonstrated that discrepancies between patient and informant ratings typically increase over time (15)(16)(17)(24)(25)(26). Such discrepancies may be caused by deteriorating insight into symptoms (27); loss of motor skills required to complete paper-based assessments; and worsening memory, which hinders the retention and retrieval of relevant information (21,28,29).…”
mentioning
confidence: 99%
“…Although these findings do not imply that either patients or caregivers were "wrong," they do highlight the discordance and potential threat to validity of assessment processes if such discrepancies are not taken into account. The discrepancies can also be important sources of clinical information, leading some researchers to recommend use of measures, such as the Neuropsychiatric Inventory and the short-form Problem Behaviors Assessment for HD (PBA-s) (29,30), that integrate patient, informant, and clinician report as well as interviewer observations. This approach to assessment helps to ensure that important patient-centered information crucial to effective care and understanding of the individual is retained but that it is combined with information from informants unaffected by HD symptoms.…”
mentioning
confidence: 99%